SEAWATER INTRUSION IN THE GROUND WATER AQUIFER IN THE KOTA BHARU DISTRICT, KELANTAN - Kamal, Mohd Asyraf; Md. Hashim, Dr; Zin, Mohd Bin (PEOPLE: International Journal of Social Sciences, 2015)
Ground water is the most valuable natural water resource to the people in Kota Bharu for the dependence on this source. This paper discusses to what extent the seawater intrusion in the well in the research area by comparing the Chloride (Cl) content with the National Drinking Water Quality Standard 1983 that states that the permitted Cl content is 250 mg/l. The three years data of the Cl concentration in the ground water were used to observe the differences that are in 1990, 1999 and 2011. The parameter of Cl was used to identify the area that has a critical intrusion. The two areas that were observed in this study are Pengkalan Chepaand Tanjung Mas. Pengkalan Chepahave five ground water observation wells that is KB 1, KB 2, KB 3, KB 4 and KB 5, while Tanjung Mashave six ground water observation wells that isKB 6, KB 9, KB 10, KB 11, KB 12 and KB 13. KB 5, KB 12 and KB 13 are considered the most problematic wells as all the Cl content from the data from the three years exceed the National Drinking Water Standard 1983. For KB 5, the Cl content in the ground water is too extreme with the reading 1,485 mg/l in the 1990 and increased to1,778 mg/l (1999), but decreased to 1485 mg/l in 2011 but still exceed the National Drinking Water Standard 1983. Ongoing observation must be done to make sure the ground water source will not be contaminated with the sea water to ensure a sustainable water resource in the future.